PESANTREN DAN KURIKULUM PEMBELAJARAN DALAM DINAMIKA POLITIK PENDIDIKAN DI INDONESIA - Ahmad Zain Sarnoto (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2014)
Talking about pesantren in the growth, pesantren is devided by two criterias such as salafi (tradisional) and kholafi (modern) pesantren. Those condition is also influential for curriculum of each pesantren , manufacture system of pesantren, educational system and type of the leadership. It is becoming the treasury of all pesantren in Indonesia to maintain pesantren existence in educational world and social religion